Socio-Cultural Factors in Uzbek and French SocioCultural Development (Diversity Research: Journal of Analysis and Trends, 2023)
In the article, we will focus on the social factors in the sociocultural development of the Uzbek and French peoples. In particular, the cultural and educational, economic and political relations of the two peoples, the new realities of the relations between the Uzbek and French peoples are highlighted.